EFEKTIFITAS KOMUNIKASI LINGKUNGAN HIDUP PADA PELAJAR SD PUTERA PERTIWI PONDOK CABE TANGERANG SELATAN: Ikhsan Fuady, Titien Yusnita, Putri Limilia - Jurnal COMMED (Prodi Ilmu Komunikasi Universitas Putera Batam, 2016)
This research has purposes; (A) measure the effectiveness of communication about the importance of theintroduction and management of waste in elementary students of Putera Pertiwi Pondok Cabe SouthTangerang, (b) identify the effectiveness of the communication on the introduction and management ofenvironmental pollution on elementary students Putera Pertiwi Pondok Cabe South Tangerang, (c) identifythe effectiveness of communication regarding to the importance of limiting consumption and wastefulbehavior of the elementary students of Putera Pertiwi Pondok Cabe South Tangerang. This study is designedas an experimental research with Quasy Experiment approach, by giving treatment by socialization ofvarious environmental issues. To measure the level of knowledge of students before and after treatment, thestudents were are given pretest and posttest using research instruments. Samples of this reasearch areelementary school students of Putera Pertiwi Pondok Cabe South Tangerang. The data were analyzed usingdescriptive statistical analysis (percentage and average / mean) and inferential analysis by paired sample Ttest.The results showed that the effectiveness of the communication environment; (1) the introduction andwaste management, (2) the introduction and management of environmental pollution, and (3)communication about the importace of restrictions on the consumption and provident behavior forelementary students by giving the tutorials, games, and discussion, have any real effect in improvingstudents'knowledge.